Bird flu : a rising pandemic in Asia and beyond? - Tambyah, Paul; Leung, Ping-Chung, 1941- (World Scientific, 2006)
Chickens cannot be bought in Vietnam restaurants for love or money. New reports are emerging every week of the global reach of avian influenza in birds. Africa and Europe are now affected by what was thought to be an Asian poultry disease. Governments worldwide are stockpiling antiviral drugs and forming rationing plans. Citizens are concerned that they will not be in "the list" of those who will receive these wonder drugs. Reports are emerging of antiviral drug resistance as the influenza virus mutates. What is the influenza virus? Why are people so worried about pandemic influenza? What is a pandemic? Will it really happen? What is the real situation of avian influenza in humans in Asia? What are governments in the region doing to control the epidemic in birds? Are we overreacting to a couple of hundred cases in humans across Asia and Europe? What if there is no pandemic? In this timely book, a group of experts from across Asia come together to answer these and other issues. While there are many questions which can never be answered, here for the first time is a series of scholarly articles written for the layperson by scientists and clinicians addressing the issues surrounding avian influenza and global pandemic influenza in humans.